Wrinkle formation in a polymeric drug coating deposited via initiated chemical vapor deposition. Issue 47 (14th November 2016) - Christian, Paul; Ehmann, Heike M. A.; Werzer, Oliver; Coclite, Anna Maria
Abstract : Polymeric encapsulation by initiated chemical vapor deposition of clotrimazole in an amorphous state results in the formation of surface wrinkles. The characteristic wrinkle length scales vary thereby as a function of the drug layer's thickness. Abstract : Polymer encapsulation of drugs is conventionally used as a strategy for controlled delivery and enhanced stability. In this work, a novel encapsulation approach is demonstrated, in which the organic molecule clotrimazole is enclosed into wrinkles of defined sizes. Having defined wrinkles at the drug/encapsulant interface, the contact between the encapsulating polymer and the drug can be improved. In addition, this can also allow for some control on the drug delivery as the available surface area changes with the wrinkle size. For this purpose, thin films of clotrimazole were deposited onto silica substrates and were then encapsulated by crosslinked poly(2-hydroxyethyl methacrylate) (pHEMA) via initiated chemical vapor deposition (iCVD). The thickness and the solid state (crystalline or amorphous) of the clotrimazole layer were varied so that the conditions under which surface wrinkles emerge can be determined. A (critical) clotrimazole thickness of 76.6 nm was found necessary to induce wrinkles, whereby the wrinkle size is directly proportional to the thickness of the amorphous clotrimazole. When the pHEMA was deposited on top of crystalline clotrimazole instead, wrinkling was absent. The wrinkling effect can be understood in terms of elastic mismatch between the relatively rigid pHEMA film and the drug layer. In the case of amorphous clotrimazole, the relatively soft drug layer causes a large mismatch resulting in a sufficient driving force for wrinkle formation. Instead, the increased elastic modulus of crystalline clotrimazole reduces the elastic mismatch between drug and polymer, so that wrinkles do not form.